It's no fun to be sick! - Barnes, Caroline; Brannon, Tom; Children's Television Workshop ([New York] : Western Pub. Co. in conjunction with Children's Television Workshop, 1989)
"Golden book." Herry thinks it looks like fun to be sick--until he gets sick.
"Featuring Jim Henson's Sesame Street Muppets."
"A Sesame Street/Golden Press book."
"A Golden book"--Cover
3.7
K-3
K-3
Keywords: Sick -- Fiction; Brothers and sisters -- Fiction; Puppets -- Fiction; Sick -- Fiction